Altered Hepatic Lipid Metabolism Contributes to Nonalcoholic Fatty Liver Disease in Leptin-Deficient Ob/Ob Mice. (25th December 2013) - Perfield, James W.; Ortinau, Laura C.; Pickering, R. Taylor; Ruebel, Meghan L.; Meers, Grace M.; Rector, R. Scott
Abstract : Nonalcoholic fatty liver disease (NAFLD) is strongly linked to obesity, insulin resistance, and abnormal hepatic lipid metabolism; however, the precise regulation of these processes remains poorly understood. Here we examined genes and proteins involved in hepatic oxidation and lipogenesis in 14-week-old leptin-deficient Ob/Ob mice, a commonly studied model of obesity and hepatic steatosis. Obese Ob/Ob mice had increased fasting glucose, insulin, and calculated HOMA-IR as compared with lean wild-type (WT) mice. Ob/Ob mice also had greater liver weights, hepatic triglyceride (TG) content, and markers of de novo lipogenesis, including increased hepatic gene expression and protein content of acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), and stearoyl-CoA desaturase-1 (SCD-1), as well as elevated gene expression of PPAR γ and SREBP-1c compared with WT mice. While hepatic mRNA levels for PGC-1 α, PPAR α, and TFAM were elevated in Ob/Ob mice, measures of mitochondrial function ( β -HAD activity and complete (to CO2 ) and total mitochondrial palmitate oxidation) and mitochondrial OXPHOS protein subunits I, III, and V content were significantly reduced compared with WT animals. In summary, reduced hepatic mitochondrial content and function and an upregulation in de novo lipogenesis contribute to obesity-associated NAFLD in the leptin-deficient Ob/Ob mouse.